Significant Trends in Portrayal of Asian American in Hollywood Films and the Role of American Perspective - Sharmaine Ibarra (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This research reexamines the relationship of reality and film through examining the significant changes in portrayal of Asian Americans in Hollywood films. The American perspective has played a critical role in portraying Asian characters in film for the longest time. However, the recent shift from portrayal of Asian-to-Asian American characters revealed that Hollywood films are slowly breaking away from dependency on American perspective. Instead, the reality that is started to be portrayed in Hollywood films is from the perspective of Asian Americans which is the long-time goal of Asian American community. The study examines the significant change in portrayal of Asian Americans in Hollywood films by classifying four periods; before 1990s, 1990s, 2000s and 2010s. Two films that represent the significant trend in each period are also analyzed. The study concluded that the increase in Asian American filmmakers and the efforts of Asian American community in utilizing technology aided the positive change. Despite of COVID-19 pandemic, positive change in portrayal of Asian Americans in Hollywood films is expected to continue through constant efforts.